LC-NMR : expanding the limits of structure elucidation - Gonnella, Nina C. (Boca Raton, FL : Taylor & Francis, 2013)
'The book is designed as a reference for chemists, NMR spectroscopists, chromatographers, students, and research professionals who are engaged in the isolation and NMR spectral characterization of complex organic molecules. The content guides the reader through the process of selecting the appropriate experiments and isolation systems while providing a foundation of basic theory and spectral interpretation. It discusses new and robust technologies that expand the limits of detection in NMR spectroscopy and includes examples of applications relevant to problems in pharmaceutical development'--
Includes bibliographical references and index.
Keywords: Liquid chromatography; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Research & Methodology; SCIENCE / Spectroscopy & Spectrum Analysis